On the economic causes of the present state of agriculture in Ireland: part six - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1849)
In this paper I propose, in the first place, to direct your attention to the special impediments to the application of capital to mining operations in Ireland, which arise from the state of the law with regard to mines. And I do so for the purpose of showing how groundlessly the case of mines has been brought forward, to prove that the state of Ireland arises from the perverse character of the people. I shall, then, conclude this series of papers, by noticing the theory that the state of agriculture in Ireland arises from a want of industrial knowledge, which is very commonly relied on as opposing the conclusions at which I have arrived.
Read April 30th 1849
Keywords: Mining; Land leasing; 314.15